Innate and adaptive effector immune drivers of cytomegalovirus disease in lung transplantation: a double-edged sword - Bharti, Reena; Calabrese, Daniel R. (Frontiers in Transplantation, 2024)
Up to 90% of the global population has been infected with cytomegalovirus (CMV), a herpesvirus that remains latent for the lifetime of the host and drives immune dysregulation. CMV is a critical risk factor for poor outcomes after solid organ transplant, though lung transplant recipients (LTR) carry the highest risk of CMV infection and CMV-associated comorbidities compared to recipients of other solid organ transplants. Despite potent antivirals, CMV remains a significant driver of chronic lung allograft dysfunction (CLAD), re-transplantation, and death. Moreover, the extended utilization of CMV antiviral prophylaxis is not without adverse effects, often necessitating treatment discontinuation. Thus, there is a critical need to understand the immune response to CMV after lung transplantation. This review identifies key elements of each arm of the CMV immune response and highlights implications for lung allograft tolerance and injury. Specific attention is paid to cellular subsets of adaptive and innate immune cells that are important in the lung during CMV infection and reactivation. The concept of heterologous immune responses is reviewed in depth, including how they form and how they may drive tissue- and allograft-specific immunity. Other important objectives of this review are to detail the emerging role of NK cells in CMV-related outcomes, in addition to discussing perturbations in CMV immune function stemming from pre-existing lung disease. Finally, this review identifies potential mechanisms whereby CMV-directed treatments may alter the cellular immune response within the allograft.